Brevican and Neurocan Cleavage Products in the Cerebrospinal Fluid - Differential Occurrence in ALS, Epilepsy and Small Vessel Disease - Hußler, Wilhelm; Höhn, Lukas; Stolz, Christopher; Vielhaber, Stefan; Garz, Cornelia; Schmitt, Friedhelm C.; Gundelfinger, Eckart D.; Schreiber, Stefanie; Seidenbecher, Constanze I. (Frontiers in Cellular Neuroscience, 2022)
The neural extracellular matrix (ECM) composition shapes the neuronal microenvironment and undergoes substantial changes upon development and aging, but also due to cerebral pathologies. In search for potential biomarkers, cerebrospinal fluid (CSF) and serum concentrations of brain ECM molecules have been determined recently to assess ECM changes during neurological conditions including Alzheimer’s disease or vascular dementia. Here, we measured the levels of two signature proteoglycans of brain ECM, neurocan and brevican, in the CSF and serum of 96 neurological patients currently understudied regarding ECM alterations: 16 cases with amyotrophic lateral sclerosis (ALS), 26 epilepsy cases, 23 cerebral small vessel disease (CSVD) patients and 31 controls. Analysis of total brevican and neurocan was performed via sandwich Enzyme-linked immunosorbent assays (ELISAs). Major brevican and neurocan cleavage products were measured in the CSF using semiquantitative immunoblotting. Total brevican and neurocan concentrations in serum and CSF did not differ between groups. The 60kDa brevican fragment resulting from cleavage by the protease ADAMTS-4 was also found unchanged among groups. The presumably intracellularly generated 150kDa C-terminal neurocan fragment, however, was significantly increased in ALS as compared to all other groups. This group also shows the highest correlation between cleaved and total neurocan in the CSF. Brevican and neurocan levels strongly correlated with each other across all groups, arguing for a joint but yet unknown transport mechanism from the brain parenchyma into CSF. Conclusively our findings suggest an ALS-specific pattern of brain ECM remodeling and may thus contribute to new diagnostic approaches for this disorder.